2015
DOI: 10.15561/18189172.2015.1004
|View full text |Cite
|
Sign up to set email alerts
|

Structural model of in-group dynamic of 6-10 years old boys’ motor fitness

Abstract: Abstract. Purpose: to determine structural model of in-group dynamic of 6-10 years old boys' motor fitness. Material: in the research 6 years old boys (n=48), 7 years old (n=45), 8 years old (n=60), 9 years' age (n=47) and10 years' age (n=40) participated. We carried out analysis of factorial model of schoolchildren's motor fitness. Results: we received information for taking decisions in monitoring of physical education. This information is also necessary for working out of effective programs of children's an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
3

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 12 publications
1
9
0
3
Order By: Relevance
“…The received results supplement scientific data about demand in structural [24,25,29] and functional analysis [16,21] of children's and adolescents' motor fitness. These results prove the idea that discriminant model [22,23,28] can be used for pedagogic control of fitness level of 16-17 years' age girls.…”
Section: Results Of the Researchsupporting
confidence: 57%
See 3 more Smart Citations
“…The received results supplement scientific data about demand in structural [24,25,29] and functional analysis [16,21] of children's and adolescents' motor fitness. These results prove the idea that discriminant model [22,23,28] can be used for pedagogic control of fitness level of 16-17 years' age girls.…”
Section: Results Of the Researchsupporting
confidence: 57%
“…The authors show potentials of classification of girls' age distinctions on the base of functional and coordination fitness testing [13]. The authors found that in factorial model of motor fitness complex training of motor abilities, general coordination; coordination of different body parts' movements, vestibular stability are distinguished [24].…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…It results not always in desirable way that is conditioned by many circumstances. In particular, health culture, as system of health control yet has not taken important place in hierarchy of demands and values of pupils and students [2,4,6,7,13,15,17,19,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%